(untitled) (Journal of the College of Education for Women, 2019)
This research deals with the technical configuration of the beautiful visions among Bany Ahmar poets reflected through the incarnation of beautiful artistic images that manifests itself clearly in the combination of two contradictories simultaneously. The main conclusion is, the Andalusian poets try to use those fictional visions in search of aesthetic pleasure and values, through forming an image from water and fire as two prominent contradicted elements to express the impact of the heat of wine which soon vanishes when it is mixed with water. By this, they show the beautiful side of nature that suggests joy and splendor.